Contesting gender: The translation of gender commitments into action in small-scale fisheries in the Pacific Islands - Lawless, Sarah (Australian Research Council Centre of Excellence for Coral Reef Studies, 2019)
Presented by Sarah Lawless (ARC Centre for Coral Reef Studies), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.